Dosimetric impact of setup errors in head and neck cancer patients treated by image-guided radiotherapy - Kaur, Inderjit (J Med Phys, 2016)
To assess and analyze the impact of setup uncertainties on target volume coverage and doses to organs at risk (OAR) in head and neck cancer (HNC) patients treated by image-guided radiotherapy (IGRT). Translational setup errors in 25 HNC patients were observed by kilovoltage cone beam computed tomography (kV CBCT). Two plans were generated. Plan one – the original plan which was the initially optimized and approved plan of the patient. All patients were treated according to their respective approved plans at a defined isocenter. Plan two – the plan sum which was the sum of all plans recalculated at a different isocenter according to setup errors in x, y, and z-direction. Plan sum was created to evaluate doses that would have been received by planning target volume (PTV) and OARs if setup errors were not corrected. These 2 plans were analyzed and compared in terms of target volume coverage and doses to OARs. A total 503 kV CBCT images were acquired for evaluation of setup errors in 25 HNC patients. The systematic (mean) and random errors (standard deviation) combined for 25 patients in x, y, and z directions were 0.15 cm, 0.21 cm, and 0.19 cm and 0.09 cm, 0.12 cm, and 0.09 cm, respectively. The study showed that there was a significant difference in PTV coverage between 2 plans. The doses to various OARs showed a nonsignificant increase in the plan sum. The correction of translational setup errors is essential for IGRT treatment in terms of delivery of planned optimal doses to target volume.